Features of Second Screen Applications - A Systematic Review - Nascimento, Francisca Joamila Brito do; Souza, Cidcley Teixeira de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
In this paper, we present a systematic literature review, whose object of study are the available features in second screen applications. The second screen is the ability to interact with the TV programming by using mobile devices. The research was conducted in order to find out what the most common features in second screen apps. The selected articles refer to 16 different features, which were grouped into 5 categories. Interactivity was the category with more features mentioned in the researched works. Therefore, we concluded the features that provide interactivity between users and TV programming are the most common on the second screen.